2010
DOI: 10.1248/bpb.33.47
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Channel Inhibitor, Verapamil, Inhibits the Voltage-Dependent K+ Channels in Rabbit Coronary Smooth Muscle Cells

Abstract: We investigated the effect of the phenylalkylamine Ca 2؉ ؉ channel inhibitor verapamil on voltage-dependent K ؉ ؉ (Kv) channels in rabbit coronary arterial smooth muscle cells using a whole-cell patch clamp technique. Verapamil reduced the Kv current amplitude in a concentration-depenent manner. The apparent K d value for Kv channel inhibition was 0.82 m mM. Although verapamil had no effect on the activation kinetics, it accelerated the decay rate of Kv channel inactivation. The rate constants of association a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Several research groups, including ours, have attempted to identify the side effects of chemicals that affect vascularKvchannelsbesidestheirownfunction.Forexample, curcumin (spice), the phosphoinositide-3 kinase inhibitor LY294002, the L-type Ca 2+ channels inhibitor verapamil, the T-type Ca 2+ channels inhibitor mibefradil, the protein kinase C inhibitor bisindolylmaleimide (I), and the guanylyl cyclase activator YC-1 directly inhibited vascular Kv channels in the open state. [26][27][28][29][30][31] In addition, the Ca 2+ channels inhibitor efonidipine and NNC 55-0396, as well as the tyrosine kinase inhibitor genistein and the protein kinase A inhibitor H-89 directly inhibited the vascular Kv channel in the closed state. 13,14,32,33) Furthermore, our group also reported that the protein kinase C inhibitor staurosporine and the calmodulin inhibitor trifluoperazine inhibited the vascular Kv channel in both open and closed states.…”
Section: Discussionmentioning
confidence: 99%
“…Several research groups, including ours, have attempted to identify the side effects of chemicals that affect vascularKvchannelsbesidestheirownfunction.Forexample, curcumin (spice), the phosphoinositide-3 kinase inhibitor LY294002, the L-type Ca 2+ channels inhibitor verapamil, the T-type Ca 2+ channels inhibitor mibefradil, the protein kinase C inhibitor bisindolylmaleimide (I), and the guanylyl cyclase activator YC-1 directly inhibited vascular Kv channels in the open state. [26][27][28][29][30][31] In addition, the Ca 2+ channels inhibitor efonidipine and NNC 55-0396, as well as the tyrosine kinase inhibitor genistein and the protein kinase A inhibitor H-89 directly inhibited the vascular Kv channel in the closed state. 13,14,32,33) Furthermore, our group also reported that the protein kinase C inhibitor staurosporine and the calmodulin inhibitor trifluoperazine inhibited the vascular Kv channel in both open and closed states.…”
Section: Discussionmentioning
confidence: 99%
“…Similar effects have been reported for other ion channel activators/ inhibitors, independently of their own functions. For example, verapamil, a phenylalkylamine Ca 2+ channel inhibitor, directly inhibits Kv and BK Ca channels in vascular smooth muscle cells (30,31) and inhibited delayed rectifier K + current in cardiac myocytes (32,33). NS 1619 and BMS-204352, BK Ca channel activators, directly inhibited the cardiac L-type Ca 2+ channel (34,35).…”
Section: +mentioning
confidence: 99%
“…The drugs that were used in the present study were: 1) inhibitors of calcium-activated-potassium channels (K Ca ); largeconductance K Ca inhibitors, iberiotoxin (IbTX; Sigma-Aldrich Japan, Tokyo, Japan) (Latorre et al, 1989;Marchenko and Sage, 1996); charybdotoxin (ChTX; Sigma-Aldrich Japan) (Miller et al, 1985); small-conductance K Ca inhibitor, apamine (Muraki et al, 1997); 2) CaCl 2 (Wako Pure Chemicals, Osaka, Japan); 3) inhibitors of L-type voltage-gated-calcium channels (Ca V ), nifedipine (Wako Pure Chemicals) (Medina et al, 2010), verapamil (Wako Pure Chemicals) (Ko et al, 2010); 4) agonist of L-type Ca V , Bay K8644 [S-(Ϫ)-1,4-dihydro-2,6-dimethyl-5-nitro-4-(2-[trifluoromethyl]phenyl)-3-pyridine carboxylic acid methyl ester] (Sigma-Aldrich Japan) (Amobi et al, 2010); 5) acidic and alkaline substances, HCl, lactic acid, NaOH, NaHCO 3 (Wako Pure Chemicals); 6) inhibitors of ion pumps: Na-pump (K ϩ -Na ϩ -ATPase) inhibitor, ouabain (Sigma-Aldrich Japan) (Briggs et al, 1996); 7) hybrid of ATP-sensitive potassium channel (K ATP ) opener and nitrate: nicorandil (Chugai Pharmaceutical Co, Tokyo, Japan) (Uchida et al, 1978;Yanagisawa et al, 1979); 8) K ATP opener, pinacidil (Wako Pure Chemicals) (Davies et al, 2010); 9) K ATP inhibitor, glibencramide (Wako Pure Chemicals) (Lindauer et al, 2003;Medina et al, 2010); 10) drugs that affect the sarcoplasmic reticulum (SR), caffeine (Wako Pure Chemicals) (Somlyo and Somlyo, 1976), dantrolene (Wako Pure Chemicals) (Kuba, 1980); 11) drugs that affect the mitochondria, oligomycin (Sigma-Aldrich Japan) (Visneskii et al, 1980); 12) ␤-adrenergic receptor agonist, isoproterenol (Sigma-Aldrich Japan) (Petkov and Nelson, 2005) Data Presentation. Because PCs of coronary artery rings obtained from the same beagle tend to provide a uniform response to a given stimulus (Uchida, 1985), each study group was composed of rings obtained from different beagles; therefore, the number of rings also indicated the number of beagles in the present study.…”
Section: Methodsmentioning
confidence: 99%